Enantioselective Desymmetrization of Prochiral Cyclohexanones by Organocatalytic Intramolecular Michael Additions to α, β‐Unsaturated Esters1. Issue 16 (27th February 2015) - Gammack Yamagata, Adam D.; Datta, Swarup; Jackson, Kelvin E.; Stegbauer, Linus; Paton, Robert S.; Dixon, Darren J.
Abstract A new catalytic asymmetric desymmetrization reaction for the synthesis of enantioenriched derivatives of 2‐azabicyclo[3.3.1]nonane, a key motif common to many alkaloids, has been developed. Employing a cyclohexanediamine‐derived primary amine organocatalyst, a range of prochiral cyclohexanone derivatives possessing an α, β‐unsaturated ester moiety linked to the 4‐position afforded the bicyclic products, which possess three stereogenic centers, as single diastereoisomers in high enantioselectivity (83–99 % ee) and in good yields (60–90 %). Calculations revealed that stepwise CC bond formation and proton transfer via a chair‐shaped transition state dictate the exclusive endo selectivity and enabled the development of a highly enantioselective primary amine catalyst.